Des pratiques pastorales plurimillénaires expliquées à la lumière des découvertes récentes sur les hormones - Anne-Marie Brisebarre (Ateliers d'Anthropologie)
In extensive breeding systems, whether sedentary or mobile, breeders often have very strong relationships with their livestock. Birth is a crucial moment: if there is a problem, the breeder or shepherd will intervene in order to create the link between the mother and her offspring, making her recognise and “adopt” the newborn. Likewise, when the female “holds back her milk” at the moment of milking, they resort to proven techniques to lead her to “give her milk”. These pastoral skills, which grew out of everyday proximity to livestock, have existed for centuries, even millennia, transmitted from generation to generation. I will provide a few examples of these manipulations of the animals’ bodies during birth or milking, observed in France, Morocco and West Africa, before discussing specialised publications from recent decades that shed light on the physiological mechanisms at play, particularly the role of oxytocin, “the attachment hormone”, whose liberation these practices encourage.